Atividades biológicas de duas espécies de Myrsine L. (Primulaceae) e de Tithonia diversifolia (Hemsl.) A. Gray (Asteraceae) - Miranda, Maria Augusta Ferraz Machado (Universidade Federal de São Carlos, 2015)
Plants species from Brazilian savanna often have defense mechanisms in response to the low nutrient content of the soil, the light intensity, the competition for resources and drought, pronounced by deep water deficit, to which they are subjected. This area is a potential source of bioactive compounds that still little explored and potential phytochemical studies of these species are important to this preservation. Biological invasions are one of the main factors threatening the Brazilian savanna biodiversity. Many plants are initially introduced as ornamental species and subsequently become invasive. Invasive plants are generally more competitive than the other species and tolerate unfavorable conditions. This advantage can be explained according to the "Novel weapons hypothesis". It proposes that invasive plants have secondary metabolites that act as allelochemicals and present new challenges to native species. Thus, secondary metabolites of invasive species in the Brazilian savanna are also an important area of phytochemistry being investigated. Therefore, we hypothesized that native species from Brazilian savanna, Myrsine umbellata and Myrsine coriacea, and the alien specie, Tithonia diversifolia, produces secondary metabolites that have different biological activities, including insecticidal, antifungal and phytotoxic acitivities, favoring their establishment in this environment and have economic importance for agriculture and pharmaceutic industry. In the Chapter 1, the biological activity of leaf extracts of M. umbellata and M. coriacea, was evaluated. The in vitro antifungal effect of leaf extracts of these two species was evaluated against Pythium aphanidermatum, Fusarium oxysporum and Colletotrichum acutatum, three important crop pathogens. We also evaluated the insecticide potential of these extracts against Spodoptera frugiperda, known as fall armyworn, an important pest that causes damages to many crops. Finally, the total polyphenols and antioxidant activity of the leaf extracts of these two species was quantified by the DPPH method. In the Charpter 2 we evaluated the phytotoxic potential of leaf, stem and root extracts from T. diversifolia. Bioassays of wheat elongation coleoptile seed germination and seedling growth are performed. The Ethyl Acetate leaf extract was the most active extract and was selected to continue the isolation studies and the identification of compounds. The chromatographic separation of this extract allowed us the isolation of 12 sesquiterpene lactones (STSs), 1 secosesquiterpeno, and 1 diterpene. Two STSs are reported for the first time in this study, 8β-O-(2-methylbutyroyl) and tirotundin 8β-O-(isovaleroyl)tirotundin. The high phytotoxic activity of the extracts and compounds, especially the majority, 1β-methoxydiversifolin, tagitinin A and tagitinin C, indicates that allelopathy may be responsible for their establishment in this habitat. In the Chapter 3, the T. diversifolia Ethyl Acetate fractions were tested for insecticidal activity against S. frugiperda and it was observed a significant reduction in the pupal weight of the caterpillar. This may be an indicative of the presence of toxic substances to this insect in these fractions, however, this reduction in the pupal weight is not associated with the majority compounds tested. Thus, we conclude that the studied plant species have secondary metabolites with promising biological activities and economic importance for agriculture and pharmaceutical industry.
Keywords: Cerrados; Invasão biológica; Metabólitos secundários; Atividade biológica; Fitoquímica; Brazilian savanna; Biological invasion; Secondary metabolites; Biological activity; Leaf extracts; Phytochemical; CIENCIAS BIOLOGICAS::ECOLOGIA